Investigation of the drying agent flow, trajectory, product span distance in the drying chamber of the A1-ARCH complex, as well as drying time - Tufekchi, Valentyn; Okopna, Yana (My University, 2019)
The milk serum contains up to 50% of dry milk substances, which is 36% of its energy value, therefore the issue of its use in food for non-waste milk processing became especially relevant. One of the most effective ways to reduce serum losses and maximize the use of all its components is to organize its processing into long-stored concentrates - dry and condensed.

Молочна сироватка містить до 50% сухих речовин молока, що становить 36% його енергетичної цінності, тому питання її використання в їжу для безвідходної переробки молока набуло особливої актуальності. Одним із найефективніших способів зменшення втрат сироватки та максимального використання всіх її компонентів є організація її переробки на концентрати тривалого зберігання - сухі та згущені.
Keywords: кафедра мехатроніки та пакувальної техніки; кафедра технологічного обладнання та комп’ютерних технологій проектування; drying agent flow; drying chamber; concentrate; milk processing; концентрат; переробка молока; потік сушильного агента; сушільна камера